Potential Fish Oil as Acute Hepatitis Candidate by Hepatoprotective Mechanism: A-review - Heru Sasongko; Muhammad Fiqri Zulpadly; Yeni Farida (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2023)
Acute hepatitis is a health concern that emerged during the COVID-19 outbreak. Toxic drugs, infections, autoimmune diseases, and other causes may induce acute hepatitis, which is deadly. Acute hepatitis isn't treatable. Renewable natural products, such as fish, are used in complementary treatment. This paper mentions current preclinical and clinical studies of omega-3 fatty acids (N-3 FAs) for hepatoprotection. The mechanism of inhibition of oxidative stress and inflammation in the liver is the subject of discussion associated with its potential as a treatment for acute hepatitis. This review article on acute hepatitis treatment analyzed original articles, books, and other relevant material from the Web of Science, Scopus, and PubMed. The literature search was conducted in April-July 2022. The keywords explored during the literature investigation were "omega-3 or EPA or DHA or fish oil," "hepatoprotective," "acute hepatitis," "inflammatory", and "stress oxidative". The study's results show that N-3 FAs can protect against liver damage through inflammation and oxidative stress pathways. Enzyme parameters of liver damage, proinflammatory cytokines, and oxidative stress can be inhibited by the administration of fish oil and its derivatives. Even though not all clinical trial parameters are directly related to animal tests, the results of this study show that omega-3 fatty acids should be considered a treatment option for acute hepatitis.